DEVELOPMENT OF A FATIGUE-RESISTANT TEST BATTERY TO ASSESS MATCH-SPECIFIC ENDURANCE AND TECHNICAL PERFORMANCE IN VOLLEYBALL - Amer Mishaal Faihan (Scholars Digest Publishing, 2025)
The physical endurance to play volleyball is not the only determining factor in volleyball game but also the capacity to employ technical finesse uptill exhaustion. Traditional tests tend to be compartmentalized into physical and technical measures, thus lacking ecological validity regarding a match to the real-life situation. The purpose of this research was to design and establish a fatigue-resistant test battery with good abilities to combine endurance and skill performance, as it is in competitive volleyball. In the conceptual framework, the aspects of repeated sprinting and shuttle run were combined with skill-based tests as the performance of serving a ball accurately and executing a spike with a time limit. Pilot research was done with a small group of athletes to better the process of executing test protocols and subsequently a larger sample was verified in 100 athletes. Physiological markers monitored included heart rate, blood lactate, and subjective measurements included Rate of Perceived Exertion and technical performance were taken pre- and post-fatigue. Mixed ANOVA was used to analyze data in order to examine interaction effects between fatigue and results of skill outcomes, and reliability indices (Intraclass Correlation Coefficient, Standard Error of Measurement) were calculated. Results indicated that the suggested battery shows high sensitivity to fatigue- induced shifts as well as great reliability in recurring trials, supplying a sensible tool to coaches and sport scientists. The proposed test battery bridges the gap between the physical and technical realms and contributes to an ecologically valid method of measuring the match-specific endurance and technical performance in volleyball, which would help decision-making during training and talent identification processes.
Keywords: Endurance, Fatigue, Performance, Reliability, Volleyball.